2018
DOI: 10.3389/fphar.2018.00541
|View full text |Cite
|
Sign up to set email alerts
|

Mining Patients' Narratives in Social Media for Pharmacovigilance: Adverse Effects and Misuse of Methylphenidate

Abstract: Background: The Food and Drug Administration (FDA) in the United States and the European Medicines Agency (EMA) have recognized social media as a new data source to strengthen their activities regarding drug safety.Objective: Our objective in the ADR-PRISM project was to provide text mining and visualization tools to explore a corpus of posts extracted from social media. We evaluated this approach on a corpus of 21 million posts from five patient forums, and conducted a qualitative analysis of the data availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 60 publications
0
46
1
3
Order By: Relevance
“…Admittedly, WEB-RADR’s focus on Twitter and Facebook limits the generalisability of this conclusion and research conducted during the WEB-RADR project and elsewhere using patient fora have identified some data-rich areas. Although the WEB-RADR study of Caster et al [15] did not show any benefit in SD performance using data from patient fora, evidence has been generated concerning methylphenidate and misuse [31, 32], and elsewhere research has shown that social media data can provide real-world use data and outcomes to inform safety decision making [11, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, WEB-RADR’s focus on Twitter and Facebook limits the generalisability of this conclusion and research conducted during the WEB-RADR project and elsewhere using patient fora have identified some data-rich areas. Although the WEB-RADR study of Caster et al [15] did not show any benefit in SD performance using data from patient fora, evidence has been generated concerning methylphenidate and misuse [31, 32], and elsewhere research has shown that social media data can provide real-world use data and outcomes to inform safety decision making [11, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have already identified ADEs reported in medical articles via NLPs [ 8 , 9 ], electronic health records [ 5 , 6 ], and social media posts [ 10 , 11 ]. An annotated corpus for the automatic detection of ADEs was created for case reports in medical articles [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing automation research targets different source materials, reflecting the wide range of signals processed by real-world postmarketing surveillance. These inputs include electronic health records [ 5 , 6 ], patient reports [ 7 ], medical articles [ 8 , 9 ], and social media posts [ 10 , 11 ]. This study focuses on medical articles as they comprise a substantial portion of postmarketing surveillance in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…In dentistry, we see this with underutilization of pit and fissure sealants despite robust evidence of their effectiveness . Misuse is the incorrect provision of care; for example, prescription of medications for the wrong purpose, dose, or duration, such as seen in the current opioid epidemic in the USA …”
Section: The Know‐do Gapmentioning
confidence: 99%